Please wait...
1800-212-7858 (Toll Free)
9:00am - 8:00pm IST all days

or

Thanks, You will receive a call shortly.
Customer Support

You are very important to us

For any content/service related issues please contact on this toll free number

022-62211530

Mon to Sat - 11 AM to 8 PM

The mth term of an AP is n and the nth term is m. Find the (m+n)th term of this AP.

Asked by Topperlearning User 22nd September 2017, 3:29 PM
Answered by Expert
Answer:

Let a and d respectively be the first term and the common difference of the AP.

Then, we have:

a + (m - 1)d = n …………(i)

And,a + (n - 1)d = m ………..(ii)

On solving (i) and (ii), we get,

d = -1 ; a = m + n - 1

am+n = a + (m + n - 1)d

= m + n -1 + (m + n - 1)(-1)

= m +n - 1 - m - n + 1

= 0

Answered by Expert 22nd September 2017, 5:29 PM
Rate this answer
  • 1
  • 2
  • 3
  • 4
  • 5
  • 6
  • 7
  • 8
  • 9
  • 10

You have rated this answer /10

Your answer has been posted successfully!